2016
DOI: 10.1038/ncomms12794
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 decreases bone mass by stimulating osteoclastogenesis and inhibiting osteoblast differentiation

Abstract: Osteoporosis is an age-related disease that affects millions of people. Growth differentiation factor 11 (GDF11) is a secreted member of the transforming growth factor beta (TGF-β) superfamily. Deletion of Gdf11 has been shown to result in a skeletal anterior–posterior patterning disorder. Here we show a role for GDF11 in bone remodelling. GDF11 treatment leads to bone loss in both young and aged mice. GDF11 inhibits osteoblast differentiation and also stimulates RANKL-induced osteoclastogenesis through Smad2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 64 publications
5
142
0
4
Order By: Relevance
“…At 10 and 21 days post‐fracture, samples were collected for radiography, microCT scanning, and histology analysis. For femoral cortical bone defect, a 1.0 mm hole was generated using a round bur (Komet ® , Germany) operating at 10,000 rpm under saline irrigation (Liu et al , ,c). Samples were harvested 2 weeks after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…At 10 and 21 days post‐fracture, samples were collected for radiography, microCT scanning, and histology analysis. For femoral cortical bone defect, a 1.0 mm hole was generated using a round bur (Komet ® , Germany) operating at 10,000 rpm under saline irrigation (Liu et al , ,c). Samples were harvested 2 weeks after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the rejuvenating effect of GDF11 was called into question by Egerman et al (5), who demonstrated that GDF11 increased with age and inhibited muscle regeneration. Correspondingly, recent studies demonstrated that GDF11 had no rejuvenating effect on aged skeletal muscle satellite cells (18) or on aging-related pathologic hypertrophy (19), but induced bone loss (20), striated muscle atrophy (21), and cardiac and skeletal muscle dysfunction and wasting (22). Furthermore, elevated GDF11 is a risk factor for age-related frailty and disease in humans (23).…”
mentioning
confidence: 99%
“…The cells were then stained with 1% Alizarin red S (pH 4.2, Sigma-Aldrich) for up to 5 minutes at room temperature15. Images of MSC stained with ARS were captured and stored digitally.…”
Section: Methodsmentioning
confidence: 99%